A nanoscale polymolybdate built by two hexavacant Keggin-type fragments via a novel Ca6P6O38 cluster with β-sheet conformation modulation ability. Issue 17 (13th April 2022) - Hua, Jiai; Wei, Xueman; Bian, Yujian; Ma, Xiang; Hao, Li; Sun, Jierui; Fan, Jingjing; Niu, Yulan; Wang, Yanqing
Abstract : A novel sandwich-type phosphomolybdate based on two hexavacant Keggin-type fragment incorporating a hexagonal calcium phosphorus oxygen cluster Ca6 P6 O38 was obtained. It can modulate the β-sheet-rich aggregates of Aβ and thus suppress the ROS produced by those toxic species. Abstract : A novel sandwich-type phosphomolybdate based on two hexavacant Keggin-type building blocks [PMo6 O28 ] 15− incorporating a novel hexagonal calcium phosphorus oxygen cluster Ca6 P6 O38 was successfully synthesized. It can modulate the β-sheet-rich misfolding conformation of Aβ that is believed to be the core structure of the toxic species in Alzheimer's disease and thus suppress the reactive oxygen species (ROS) produced by those harmful aggregates.